2012
DOI: 10.1007/s13770-012-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of bone marrow-derived mesenchymal stem cells and platelet-rich plasma on bone regeneration of calvarial defects in rabbits

Abstract: Bone tissue regeneration techniques include tissue engineering approaches which employ mesenchymal stem cells as an osteogenic agent for bone repair. Recent studies have demonstrated that tissue engineering scaffolds and growth factors can support cell proliferation, bone formation, and bone tissue repair in lost bone tissue. Furthermore, many studies have suggested that platelet-rich plasma (PRP) can improve bone regeneration due to the numerous growth factors that it contains. This study was performed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…However, it led to relatively higher amounts of bone formation after just 21 days and if the samples were assessed for a longer period of time, it might have made a bigger difference. Similar results were obtained by Yun et al, who investigated synergistic effects of BMMSCs and Platelet-Rich Plasma (PRP) on bone regeneration [24]. They used calvarial defects of 6 mm diameter and hydroxyapatite as the scaffold for MSCs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, it led to relatively higher amounts of bone formation after just 21 days and if the samples were assessed for a longer period of time, it might have made a bigger difference. Similar results were obtained by Yun et al, who investigated synergistic effects of BMMSCs and Platelet-Rich Plasma (PRP) on bone regeneration [24]. They used calvarial defects of 6 mm diameter and hydroxyapatite as the scaffold for MSCs.…”
Section: Discussionsupporting
confidence: 77%
“…However, they reported significantly higher bone formation in the experimental group after 12 weeks. Additional studies that also reported similar short term results in regards to application of MSCs in rabbits, indicate that using MSCs in regards to improving bone regeneration requires more than 3 weeks to be efficient [24]. However, in a recent experimental study Choi et al reported significantly higher amount of bone formation just after 2 weeks by using adipose-derived mesenchymal stem cell seeded ADM on 4 mm calvarial defects of mice [11].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been also demonstrated that bone regeneration and cell proliferation in lost bone tissue can be enhanced by the application of tissue engineered scaffolds (Yun et al 2012). PLGA has been considered as a popular polymer in the tissue engineering field.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that they also aid in the transport of GFs at the beginning of the healing processes [39]. Platelets may act as natural biological mediators, regulating cellular processes during tissue regeneration, including chemotaxis, extracellular matrix differentiation, and synthesis, by binding to specific cell surface receptors [40].…”
Section: Guided Bone Regeneration Based On Platelet-rich Plasma (Prp)mentioning
confidence: 99%